Electrochemical detection of tocopherols in vegetable oils by supercritical fluid chromatography equipped with carbon fiber electrodes. Issue 36 (3rd September 2018) - Yamamoto, Kazuhiro; Kotani, Akira; Hakamata, Hideki
Abstract : The oxidation current of tocopherol was obtained by a flow-through column electrolytic cell in supercritical carbon dioxide. Abstract : A flow-through column electrolytic cell for supercritical fluid chromatography has recently been developed. To examine the applicability of the cell to real samples, the determination of tocopherols in edible vegetable oils was carried out. Tocopherols (α, β, γ and δ) and 2, 2, 5, 7, 8-pentamethyl-6-hydroxychroman (internal standard) were eluted and fully separated within 10 min using a mixture of supercritical carbon dioxide and methanol containing 1.0 mol L −1 ammonium acetate (98 : 2, v/v) as a mobile phase and a conventional silica gel column as a stationary phase. The current peak area detected in the electrochemical cell was found to be linear with the amount of samples injected in the range from 5 μmol L −1 to 200 μmol L −1 ( r ≧ 0.997). The repeatability was not more than 1.82% RSD ( n = 6) and the intermediate precision was also not more than 3.55% RSD ( n = 3). The limit of detection ( S / N = 3) on the column was less than 3.43 pmol. By the present internal standard method, tocopherols in various vegetable oils were determined with a simple sample preparation procedure.